A novel collection optimisation solution maximising long-term profits: a case study in an international bank. Issue 4 (2nd October 2017) - Duman, Ekrem; Ecevit, Fatih; Çakır, Çağrı; Altan, Orhan
Abstract: When customers fail to pay the amount they owe to their bank related with a credit product (credit cards, overdraft accounts or instalment loans), the bank starts the collection process. This process typically lasts for a particular amount of time after which the customer is labelled as defaulted and a litigation period is launched. Banks try to minimise the percentage of credit exposure that goes to litigation since it negatively affects the bank's profitability. Accordingly, they take various actions to maximise the collections before litigation. In this study, we approach this problem from a different perspective as we maximise not the short-term collections but the long-term revenues from customers by incorporating the churn effects of these actions in our modelling.